薬剤動態に基づいたPETアミロイドイメージングの参照領域自動設定法の精度検証 - 永岡, 隆; 岡田, 志麻; 山田, 誉大; 細川, 知紗; 石井, 一成; 木村, 裕一 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
A deposit of amyloid β (Aβ) to the central nervous system causes Alzheimer's disease (AD). A periodical evaluation on Aβ, a year, can therefor detect the beginning of AD, and it realizes an effective medical treatment for AD. For quantitative measurement of Aβ deposit is available using PET, and it requires to delineate the cerebellum gray matter as a reference region, when no Aβ deposit occurs physiologically and it has complicated shape. This study aim at proposing automated delineation algorithm based on a kinetics of administered PET tracer for Aβ imaging. The validation using a clinical data presented no significant difference (p < 0.05) between the amount of Aβ deposit using an ordinary manual delineation and the automated method. We can conclude that the algorithm is clinically useful.